Understanding How Investigative Auditors' Competence, Independence, and Experience Affect the Efficiency with Which Audit Procedures are Implemented in Fraud Proof - Dyah Sisca Putri Pramesti; Poppy Sofia Koeswayo; Sony Devano (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Fraud is increasingly widespread in Indonesia. In detecting and proving fraud, a special audit is needed, namely an investigative audit. Auditors who carry out investigative audits are called investigative auditors. This study aims to determine the effect of investigative auditor competence on the effectiveness of audit procedures in proving fraud, the effect of investigative auditor independence on the effectiveness of audit procedures in proving fraud, the effect of investigative auditor experience on the effectiveness of audit procedures in proving fraud, the effect of auditor experience on auditor competence. , and the influence of investigative auditor competence on the effectiveness of the implementation of audit procedures in proving fraud through auditor experience. This study uses a quantitative research method using primary data obtained from the results of questionnaires distributed to investigative auditors at the Supreme Audit Agency (BPK RI). The population in this study is the Main Investigation Auditorate at the Supreme Audit Agency of the Republic of Indonesia. The sample used is the Main Investigation Auditorate at BPK RI. The data analysis technique used is path analysis with a significance level of 5% using SPSS 26 software. The results of this study are that the competence of investigative auditors has a positive effect on the effectiveness of implementing audit procedures in proving fraud, the independence of investigative auditors has a positive effect on the effectiveness of implementing audit procedures in proving fraud, the experience of investigative auditors has a positive effect on the effectiveness of implementing audit procedures in proving fraud, there is a positive effect of auditor experience on auditor competence, and the experience of investigative auditors has a positive effect on the effectiveness of implementing audit procedures in proving fraud through auditor competence.